The Importance Of Implementing Effective Management Mechanisms In Educational Organizations (Pedagogical Cluster-Journal of Pedagogical Developments, 2025)
This article analyzes the importance of implementing effective management mechanisms in general secondary schools. The main directions of effective management, such as strategic planning, development of material and technical base, working with teachers, cooperation with parents, and evaluating educational outcomes, are highlighted. Practical recommendations aimed at improving the effectiveness of schools are provided in the article.